Developing a Modern Dance Distance Learning System: Enhancing Interactive Sports Education with WEB3D Technology - De Zeng, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
Modern dance distance learning systems often face challenges such as limited user requirement analysis and insufficient system functionality, leading to delays and inefficient performance. These issues are particularly critical in interactive sports education, where real-time responsiveness and engagement are essential. To address the problems of delay and low CPU utilization in multimedia teaching, this study introduces a modern dance distance learning interactive system based on WEB3D technology. By analyzing user requirements and system functionality, appropriate applications were selected, and the system's functional and overall design was optimized. The implementation of WEB3D technology enhances interactivity and improves students' learning efficiency, facilitating an immersive and engaging learning experience. Experimental results demonstrate that the system performs well in terms of response time, video transmission delay, CPU utilization, and scalability, proving its high feasibility and adaptability to modern sports education needs. This study provides valuable insights into the integration of advanced technologies in sports and dance education, promoting interactive learning and performance enhancement. The findings underscore the potential of WEB3D-based systems in fostering engagement, improving cognitive and physical skills, and advancing the scope of remote sports education.